Room Temperature Deformation and Superelastic Behavior of TLM Titanium Alloy Under Different Solution Conditions - Cheng, Jun; Li, Jinshan; Yu, Sen; Du, Zhaoxin; Zhang, Xiaoyong; Gai, Jinyang; Fan, Jiangkun; Zhang, Wen; Song, Hongjie; Yu, Zhentao (Frontiers in Materials, 2020)
Metastable β-type Ti-Nb based alloys are extensively applied in the fields of surgical implantation and wound repair owing to their low elastic modulus, excellent biocompatibility as well as superelastic properties. Based on the d-electron theory, a novel metastable β-type Ti-25Nb-3Zr-2Sn-3Mo (wt %) (TLM) alloy was developed using the Bo (d orbital electron bonding strength) -Md (d electron bonding energy) diagram. The microstructures and phase constituents of the prepared alloys under different solution conditions were investigated. The unidirectional tensile tests and cyclic loading-unloading experiments were conducted to analyze the mechanical behavior and superelastic behavior. Moreover, the microstructural characteristics near the fracture for the samples under different solution conditions were also investigated. Such results show that α" quenched martensite phase is generated within the equiaxed β grains of the TLM alloys which are solution-treated in the β or (α+β) phase regions. The typical double yielding of the TLM alloys is presented during the deformation at room temperature. The alloy solution-treated at 750 °C has the strain hardening rate of approximately 1100 MPa and the uniform elongation of approximately 32.5 %. The stress-induced martensite phase and deformation twins are simultaneously generated in the microstructures of the TLM alloys during the deformation. Such alloys exhibit a certain superelastic effect due to the reverse transformation between the stress-induced martensite α" phase and β parent phase during the cyclic loading-unloading at room temperature. Furthermore, the underlying relationship between the properties of the TLM alloys and their microstructures are discussed.